2010
DOI: 10.1111/j.1469-7998.2010.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between habitat preferences and home‐range size: a case study on a large mobile colubrid snake from North America

Abstract: Effective wildlife conservation plans should consider both the habitat needs and spatial requirements of the species in question. Studies that focus on the correlation between the habitat preferences and movement patterns of wildlife, particularly snakes, are uncommon. We attempted to determine how habitat preferences or quality influenced movement patterns of snakes. To answer this question, we created a case model that incorporated habitat preference or avoidance information rigorously obtained for bullsnake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 48 publications
0
15
0
2
Order By: Relevance
“…Other radio-telemetry studies have documented transient behavior in reptiles (Kiester et al 1982, Lovich 1990), but strong annual home range overlap in snake D precludes this as an explanation for increased movements. Questions remain regarding within-population variation in spatial use (Diffendorfer et al 2005, Kapfer et al 2010.…”
Section: Scalementioning
confidence: 99%
“…Other radio-telemetry studies have documented transient behavior in reptiles (Kiester et al 1982, Lovich 1990), but strong annual home range overlap in snake D precludes this as an explanation for increased movements. Questions remain regarding within-population variation in spatial use (Diffendorfer et al 2005, Kapfer et al 2010.…”
Section: Scalementioning
confidence: 99%
“…Although habitat quality is most often, and directly, expressed as food availability (Carbone & Gittleman ), other measures of quality include available shelter (Sprent & Nicol ), level of disturbance (Kapfer et al . ), vegetative cover (McLoughlin et al . ) and proportion of open water (Fortin, Blouin‐Demers & Dubois ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on reptile spatial ecology has documented either reduced space-use 312 (Mitrovich et al 2009, Hoss et al 2010, Breininger et al 2011, Lomas et al 2019) or reduced movement 313 (Parent and Weatherhead 2000, Corey and Doody 2010, Beale et al 2016, Doherty et al 2019) in 314 fragmented agricultural landscapes. But the response to fragmentation is not universal, other research 315failed to detect significant shifts in movement patterns(Row et al 2012, Wolf et al 2013 and Diffendorfer 2015), or even revealed increased space-use in fragmented areas(Kapfer et al 2010, 317 Ettling et al 2013, potentially due to species-specific evolutionary history traits(Fahrig 2007). King 318Cobras appeared to be reacting in a way consistent with forest specialists, or taxa that have evolved in 319 continuous habitat(Fahrig 2007) -limited boundary avoidance, large movements, and mortality in 320 human-dominated areas(Marshall et al 2018).…”
mentioning
confidence: 99%